Life-cycle incidence of family policy measures in Germany: Evidence from a dynamic microsimulation model - Holger Bonin; Karsten Reuss; Holger Stichnoth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper quantifies the life-cycle incidence of key family policy measures in Germany. The analysis is based on a novel dynamic microsimulation model that combines simulated family life-cycles for a base population from the 2009 wave of the German Socio-Economic Panel (SOEP) with a comprehensive tax-benefit model. The results indicate that households in Germany benefit considerably from family- and marriage-related transfers, yet also reveal substantial variation behind the population average. Moreover, it is shown that some measures, such as income tax splitting, may make individuals in fact worse off, in financial terms, over the long course, as a result of negative labour supply incentives which are reinforced through detrimental effects on human capital accumulation.
urn:nbn:de:bsz:180-madoc-394494
Keywords: C53; C54; J12; J13; J22; 330; Dynamic Microsimulation; Family Policy; Germany